1996
DOI: 10.1002/ange.19961081121
|View full text |Cite
|
Sign up to set email alerts
|

Synthese von Glycopeptiden und Lipopeptiden durch chemoselektive Verknüpfung

Abstract: Vollständig ungeschützte Peptide mit chemoselektiv zugänglichen Gruppen reagieren unter sehr milden Bedingungen mit freien reduzierenden Zuckern oder Lipidaldehyden. Damit ergibt sich ein einfacher Zugang zu komplexen Glycopeptiden wie 1, einem Somatostatin‐Analogon, und Lipopeptiden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…[13,14] Recently, it was also reported that combined use of the glycoblotting by oxylamino-containing polymers and MALDI-TOF/TOF mass spectrometry allows for both facile purification and precise analysis of common oligosaccharides and glycopeptides from human serum or mouse skin glycoproteins. [11,15] In this study, two unnatural amino acids, 2-amino-4-O-(N-methylaminooxy) butanoic acid (1) and 2-amino-4-aminooxy butanoic acid (2), were employed for the synthesis of novel aminoacyl-tRNA (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[13,14] Recently, it was also reported that combined use of the glycoblotting by oxylamino-containing polymers and MALDI-TOF/TOF mass spectrometry allows for both facile purification and precise analysis of common oligosaccharides and glycopeptides from human serum or mouse skin glycoproteins. [11,15] In this study, two unnatural amino acids, 2-amino-4-O-(N-methylaminooxy) butanoic acid (1) and 2-amino-4-aminooxy butanoic acid (2), were employed for the synthesis of novel aminoacyl-tRNA (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…N-Methyl-N-tert-butoxycarbonylhydroxylamine (86 mg, 0.27 mmol) was added to the solution, and the mixture was stirred at 0 8C for 1 h. To the mixture was added ice water and the mixture was extracted with ethyl acetate. 28 (m, 2 H, b-H 2 ), 1.46 (s, 9 H, (CH 3 ) 3 -C-); 13 , detection at 260 nm), the products with the retention time of 14.2 and 14.5 min were collected as the two positional (2',3') isomers. After 2 h, Et 2 O (1 mL) was added to the solution and then the precipitation was collected by a centrifugation (20 000 g, 4 8C, 5 min).…”
Section: -(Pent-4-enoyl)amino-4-[o-(n-methyl-n-tert-butoxycarbonyl)amentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Solid-phase chemical methods are gaining importance as a tool enabling the study of these processes. [4] Chemoselective coupling of unprotected carbohydrates to, for example, polymeric supports, [5][6][7] microarrays, [8][9][10] peptides and proteins, [11] and to other surfaces [12] through oxime formation has been widely exploited in recent years as a means to capture glycans from natural sources and to obviate laborious glycosylation and protecting-group chemistry. The reaction exploits the unique availability of an aldehyde moiety in the reducing-end of glycans, which also allows, for example, reductive amination, hydrazone and acyl hydrazone formation, and thiazolidine formation.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Mutter reported that aminooxyl groups are also reactive with the hemiacetal of the carbohydrate through a stable oxime bond. [8] Herein, we present an effective and practical trapand-release method based on chemoselective ligation of carbohydrates with oxylamino groups attached to the surface of nanoparticles ( Figure 1) and describe the optimal conditions for glycoblotting and the versatility of this method. We have chosen an oxylamine-functionalized photopolymerizable lipid as an anchor molecule for capturing oligosaccharides.…”
Section: Introductionmentioning
confidence: 99%